Stable Isotope Trajectory Analysis (SITA): A new approach to quantify and visualize dynamics in stable isotope studies. Issue 2 (3rd February 2022) - Sturbois, Anthony; Cucherousset, Julien; De Cáceres, Miquel; Desroy, Nicolas; Riera, Pascal; Carpentier, Alexandre; Quillien, Nolwenn; Grall, Jacques; Espinasse, Boris; Cherel, Yves; Schaal, Gauthier
Abstract: Ecologists working with stable isotopes have to deal with complex datasets including temporal and spatial replication, which makes the analysis and the representation of patterns of change challenging, especially at high resolution. Due to the lack of a commonly accepted conceptual framework in stable isotope ecology, the analysis and the graphical representation of stable isotope spatial and temporal dynamics of stable isotope value at the organism or community scale remained in the past often descriptive and qualitative, impeding the quantitative detection of relevant functional patterns. The recent community trajectory analysis (CTA) framework provides more explicit perspectives for the analysis and the visualization of ecological trajectories. Building on CTA, we developed the Stable Isotope Trajectory Analysis (SITA) framework, to analyze the geometric properties of stable isotope trajectories on n‐dimensional ( n ≥ 2) spaces of analysis defined analogously to the traditional multivariate spaces (Ω) used in community ecology. This approach provides new perspectives into the quantitative analysis of spatio‐temporal trajectories in stable isotope spaces (Ωδ ) and derived structural and functional dynamics (Ωγ space). SITA allows the calculation of a set of trajectory metrics, based on either trajectory distances or directions, and new graphical representation solutions, both easily performable in an R environment. Here, we illustrate the use of our approach by reanalyzing previously published datasets from marine, terrestrial, and freshwater ecosystems. We highlight the insights provided by this new analytic framework at the individual, population, community, and ecosystems levels, and discuss applications, limitations, and development potential.